2014
DOI: 10.1055/s-0034-1365281
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events in older patients undergoing ERCP: a systematic review and meta-analysis

Abstract: Background and study aims: Biliary and pancreatic diseases are common in the elderly; however, few studies have addressed the occurrence of adverse events in elderly patients undergoing endoscopic retrograde cholangiopancreatography (ERCP). Our objective was to determine the incidence rates of specific adverse events in this group and calculate incidence rate ratios (IRRs) for selected comparison groups. Patients and methods: Bibliographical searches were conducted in Medline, EMBASE, and Cochrane library data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 78 publications
(224 reference statements)
3
49
0
Order By: Relevance
“…The lower bleeding rate in elderly patients compared with that reported by Day et al [3] may be related to the reduced ES size and the more homogeneous comparative groups in this study (both groups had similar stone characteristics). The absence of cardiopulmonary events may be explained by the lower need for mechanical lithotripsy [8,9] and the reduced mean procedure time [10] required for EPLBD.…”
supporting
confidence: 42%
See 2 more Smart Citations
“…The lower bleeding rate in elderly patients compared with that reported by Day et al [3] may be related to the reduced ES size and the more homogeneous comparative groups in this study (both groups had similar stone characteristics). The absence of cardiopulmonary events may be explained by the lower need for mechanical lithotripsy [8,9] and the reduced mean procedure time [10] required for EPLBD.…”
supporting
confidence: 42%
“…A recent systematic review [3] reported adverse events in older patients undergoing ERCP, concluding that the incidence and risk of developing specific adverse events vary by age. Elderly patients more frequently have morbid underlying diseases, periampullary diverticula, and large multiple common bile duct stones, all of which increase procedure complexity and risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the risk seems to decrease with age, confirming the findings of others. 7,12,21,[23][24][25][26] The pathophysiology behind that observance remains unclear. One explanation could be reduced levels of pancreatic enzyme secretion or more advanced atrophy of the pancreas in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,30,[36][37][38] Post-ERCP pancreatitis was defined as the onset of typical abdominal pain with an at least 3-fold elevation of serum lipase levels within 48 hours after the procedure. Perforation was defined as retroperitoneal or bowel-wall perforation identified during the procedure macroscopically or by radiologic imaging after the procedure.…”
Section: Adverse Eventsmentioning
confidence: 99%